ANALISIS TINGKAT KUALITAS PELAYANAN JASA TV KABEL DAN INTERNET PADA PT. MALANG MULTIMEDIA MANDIRI - Aditama, Roni Angger (The Studies of Social Sciences, 2019)
In this globalization era, the development of information technologcy and communication have raised too, and become an important need by the society. It was becoming a trigger of high competition between cable television and internet service providers. Several ways are done for improving the service quality toward customers. The dimension of services quality are such as tangibles factor, reliability factor, responsiveness factor, assurance factor, and empathy factor. To measure the level of service quality, this research was done in PT. Malang Multimedia Mandiri by taking 100 respondents. Questionnaire was used to collect data and analyzed by descriptive quantitative method. The result of validation test state that the whole attributes are valid by r count > r table that is more than 0.195. By using reliability test stated that the result was reliable with the score of cronbach’s alpha > 0.60. Then,continue with frequency distribution analysis by using IBM SPSS Software version 25 and the result shows that the service quality are good.